1999
DOI: 10.1073/pnas.96.17.9465
|View full text |Cite
|
Sign up to set email alerts
|

Aeolotopic interactions of globular proteins

Abstract: Protein crystallization, aggregation, liquidliquid phase separation, and self-assembly are important in protein structure determination in the industrial processing of proteins and in the inhibition of protein condensation diseases. To fully describe such phase transformations in globular protein solutions, it is necessary to account for the strong spatial variation of the interactions on the protein surface. One difficulty is that each globular protein has its own unique surface, which is crucial for its biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
220
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(229 citation statements)
references
References 20 publications
7
220
0
Order By: Relevance
“…Indeed, in such a model a change in the attractive energy as a result of the mutation must have a proportional effect on both the coexistence curve and the solubility line. In reality, however, as we have emphasized previously (37), the interprotein interactions are highly anisotropic and localized. The analysis of our data indicates that a mutation at site 23 dramatically affects the temperature dependence of the interprotein interaction.…”
Section: [4]mentioning
confidence: 78%
See 2 more Smart Citations
“…Indeed, in such a model a change in the attractive energy as a result of the mutation must have a proportional effect on both the coexistence curve and the solubility line. In reality, however, as we have emphasized previously (37), the interprotein interactions are highly anisotropic and localized. The analysis of our data indicates that a mutation at site 23 dramatically affects the temperature dependence of the interprotein interaction.…”
Section: [4]mentioning
confidence: 78%
“…This observation finds its natural explanation in the framework of the aeolotopic model (37). In this model, we have shown that the thermodynamic properties of the liquid phase can be described by a spatial thermodynamic average of the highly anisotropic actual potential.…”
Section: [4]mentioning
confidence: 93%
See 1 more Smart Citation
“…In a rough approximation, proteins can be regarded as patchy particles since their interactions are short-ranged and highly directional. [6][7][8] The study of patchy interactions can therefore be helpful in understanding the mechanisms of protein crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, theoretical calculations based on anisotropic attractive interactions successfully describe both the width of the binodal and the gap between the binodal, and the fluid-solid transition for aqueous protein solutions without additives. 60,79,80 Anisotropic attractive interactions are indeed induced by hydrophobic patches on the lysozyme surface, and have been taken into account in a patchy sphere model by Curtis et al 81 Anisotropic attractions as well as repulsions, e.g., as due to an anisotropic charge distribution or van der Waals interaction, are not taken into account in our DLVO model. Our model furthermore neglects nonelectrostatic contributions to the lysozyme pair potential that originate from dispersion forces between the micro-ions and proteins.…”
mentioning
confidence: 99%